Pengalaman Guru Sekolah Dasar dalam Mengajar Geometri - Suci Tuningsih; Hani Widyastuti (Elementary School and Education Journal, 2025)
Students' difficulties in understanding abstract geometric concepts and the occurrence of student misconceptions in geometry materials are important concerns for elementary school teachers. Teachers have a crucial role in introducing and developing students' understanding of geometric concepts. This study aims to explore the experiences of elementary school teachers in teaching geometry. This qualitative study using a narrative inquiry approach involved in-depth and structured interviews with 6 elementary school teachers from various backgrounds and teaching experiences. The results of the study showed that there were several main themes including the challenges of elementary school teachers in explaining abstract geometric concepts, effective teaching strategies, and the importance of using teaching aids in teaching geometry. To overcome the existing challenges, a creative and innovative approach is needed. The use of teaching aids, technology and active learning methods can also help improve students' understanding of geometric concepts. Teachers also emphasized the need for ongoing professional development and good curriculum support. These findings provide valuable insights for improving geometry teaching at the elementary school level and can be used to develop more effective teacher training programs.